Penguatan Kader Sebaya sebagai Upaya Pencegahan Anemia di Pondok Pesantren - Tina Yuli Fatmawati; Andicha Gustra Jeki; Maryam Novitasari; Nel Efni (Jurnal Abdimas Kesehatan (JAK), 2026)
Anemia is a nutritional problem still widely experienced by adolescent girls. Adolescent girls are categorized as anemic if their hemoglobin (Hb) level is less than 12 g/dL. Iron deficiency anemia is the most common type of anemia and is generally caused by blood loss during menstruation and increased iron requirements during growth. Anemia prevention efforts require a sustainable approach, one of which is through empowering peer cadres. This community service activity aims to strengthen the role of peer cadres in anemia prevention at the Al Hidayah Islamic Boarding School in Jambi City. The target group is 13 adolescent girls who are prepared as peer cadres through Focus Group Discussion (FGD), education, and mentoring methods. The material provided includes the definition of anemia, its causes, signs and symptoms, impacts, prevention, and the role of cadres in health education. The results of the activity indicate the formation of peer cadres as agents of change in the Islamic boarding school environment. In addition, there was an increase in cadres' knowledge about anemia and its prevention efforts after participating in the strengthening activities. cadres are expected to be able to become sources of information and motivators for their peers in implementing anemia prevention behaviors sustainably. This peer cadre strengthening program can be an effective youth empowerment strategy in supporting anemia prevention in Islamic boarding school environments.